Association between maternally perceived quality and pattern of fetal movements and late stillbirth - Billie F. Bradford (Nature Portfolio, 2019)
Abstract We investigated fetal movement quality and pattern and association with late stillbirth in this multicentre case-control study. Cases (n = 164) had experienced a non-anomalous singleton late stillbirth. Controls (n = 569) were at a similar gestation with non-anomalous singleton ongoing pregnancy. Data on perceived fetal movements were collected via interviewer-administered questionnaire. We compared categorical fetal movement variables between cases and controls using multivariable logistic regression, adjusting for possible confounders. In multivariable analysis, maternal perception of the following fetal movement variables was associated with decreased risk of late stillbirth; multiple instances of ‘more vigorous than usual’ fetal movement (aOR 0.52, 95% CI 0.32–0.82), daily perception of fetal hiccups (aOR 0.28, 95%CI 0.15–0.52), and perception of increased length of fetal movement clusters or ‘busy times’ (aOR 0.23, 95%CI 0.11–0.47). Conversely, the following maternally perceived fetal movement variables were associated with increased risk of late stillbirth; decreased frequency of fetal movements (aOR 2.29, 95%CI 1.31–4.0), and perception of ‘quiet or light’ fetal movement in the evening (aOR 3.82, 95%CI 1.57–9.31). In conclusion, women with stillbirth were more likely than controls to have experienced alterations in fetal movement, including decreased strength, frequency and in particular a fetus that was ‘quiet’ in the evening.